(untitled) (Research, Society and Development, 2022)
Objective: To analyze the knowledge of people aged 60 years or over about the geriatric specialty and their motivation to seek specialized care from a geriatrician. Methodology: This is a qualitative, quantitative, descriptive, analytical and cross-sectional study. Sample: 357 elderly, confidence level: 95% (z = 1.96), E = 5%, p = 0.23 and N = 5000. A questionnaire was used as a research instrument. Results: 55.5% totally agreed about the existence of a specialty to care for aging, 75.4% totally disagreed about the recommendation of a professional to see a geriatrician, 15.4% had a consultation with this professional, 40.6% some limitation in seeing a geriatrician, including transport, distance and income as the factors most identified by respondents. Conclusion: For the elderly included in this study, there is as much knowledge in knowledge about geriatrics as there is motivation for these elderly people to consult a geriatrician.